Strategic Planning and Sustainable Organizational Performance - Owalo, Okech Eliud; Aosa, Evans (European Journal of Business and Strategic Management, 2025)
Purpose: The research links strategic planning to sustainable organizational performance. Methodology: The methodology constituted a critical literature review linking strategic planning and leadership to organizational performance, while considering environmental dynamism. It’s anchored on the Industrial Organizational Economic Theory, focusing on both public and private sectors; plus transformational leadership theory, and environmental dependence theory. Findings: While past literature divulges lack of consensus on how deliberate strategic planning influences organizational performance, the moderating implications of environmental dynamism on organizational performance is not conceptually evident. The literature contends that strategic planning positively influences organizational performance; transformational leadership contributes to organizational performance; while environmental dynamism influences the impression of leadership on organizational performance. However, it depicts a partial focus on the link of strategic planning to performance, leadership and performance, and environmental dynamism and performance or a combination of the two and performance. Unique Contributions to Theory, Practice and Policy: From a conceptual perspective therefore, it would be interesting to comprehensively study the implications of strategic planning, and leadership on organizational performance where environmental dynamism variables are moderating factors. It is anticipated that the findings from this research will endeavor to advance scholarship, particularly on understanding the influence of strategic planning practices, transformational leadership, and environmental dynamism on organizational performance, in both the private and public sectors. Hence; how does the underlying effect of environmental dynamism on leadership, for example, manifest in strategic planning practices?